Microbiological Evaluation of the Extension Wire and Percutaneous Epidural Lead Anchor Site Following a "2‐Stage Cut‐Down" Spinal Cord Stimulator Procedure. Issue 7 (30th December 2016) - Lalkhen, Abdul Ghaaliq; Chincholkar, Mahindra; Patel, Jiten
Abstract: Objectives: There are concerns regarding bacterial colonization of the temporary extension leads and subsequent infection risk using the 2‐stage cut‐down approach in spinal cord stimulation (SCS). We sought to quantify the extent of bacterial colonization of the temporary extension wire and percutaneous epidural lead anchor site. Materials and Methods: We conducted a cross‐sectional observational study recruiting a pragmatic sample of 25 consecutive patients listed for a cut‐down trial of SCS. We excluded patients undergoing revision procedures and those who had previously received a spinal cord stimulator. The primary outcome measure was the rate and type of colonization of the extension wires and lead anchor site. Results: No surgical site infections were recorded in any of the patients and no late infections subsequent to insertion of the implantable pulse generator. Overall, 24% of patients grew organisms from the temporary extension wire. Five patients grew coagulase‐negative Staphylococcus aureus, and 1 patient grew Enterococcus faecalis . There were no positive wound cultures from the anchor site of the epidural lead. Conclusions: Despite the high colonization rate of the temporary extension wire, there were no surgical site infections. We conclude that provided appropriate strategies for the management of surgical site infections are implemented, the 2‐stage cut‐down procedure is a safe approach that is not associated with a higher incidence of infection.